Um estudo sobre a atividade do professor coordenador da escola p??blica paulista - Mello, M??rcia Nat??lia Motta (2010)
This dissertation is the result of a bibliographical and documental research which objective is to investigate the occurence of alienation in teacher coordinating public school of S??o Paulo, in its legal attributions. The aim of the study is the whole activity of this professional prescript in the state legislation from 1990, analised by the point of view of Marx s theory of Alienation, studied by M??sz??ros. The dissertation relates the activity of teacher coordinating public school with the public employees, and with the mediation in the second instance made by this professional. The research is based on the study of the legislation about teacher coordinating public school in the state of S??o Paulo, in the Loyolla collection called Orienta????o Educacional e Pedag??gica and articles and dissertations about Alienations Theory, that is the category of analisis of this dissertation.